Karbon Dots sebagai Sistem Penghantaran Obat Cerdas Berbasis Nanoteknologi - Permadi, Adi (Journal of Industrial Process and Chemical Engineering (JOICHE), 2025)
Carbon dots (CDs) are carbon-based nanomaterials smaller than 10 nm that exhibit strong fluorescence, excellent chemical stability, and environmental friendliness, making them promising candidates for diverse applications. This paper discusses the synthesis methods of carbon dots, particularly bottom-up techniques such as pyrolysis and hydrothermal synthesis, using eco-friendly precursors like agricultural and food waste. CDs are characterized by techniques including FTIR, UV-Vis, and TEM to reveal their structural and optical properties. CDs have various applications, including heavy metal sensing, bioimaging, and antimicrobial agents. The key advantages of CDs include low production costs, abundant raw materials, and high biocompatibility. This study highlights the great potential of CDs in supporting environmentally friendly technologies and encourages further research on their functionalization and future applications.